Effect of an Educational Intervention based on the Transtheoretical Model on Vitamin Intake in Female Adolescent - Eybpoosh S; Rahnavard Z; Yavari P; Rajabi F (Tehran University of Medical Sciences, 2010)
Background & Aim: Micronutrients deficiency is one of the most common health problems among adolescents. Theory based educational interventions which address learners' preferences are among the solutions for the matter in hand. The aim of this study was to determine the effectiveness of the Transtheoretical model (TTM) based educational package on vitamin intake in female adolescents in Tehran. Methods & Materials: A randomized community trial was applied. Study samples were consisted of 80 female students from two middle schools of Tehran, district 17th. They were selected using a cluster-random sampling method and were randomly assigned to the intervention (n=40) and control groups (n=40). The intervention group received a TTM-based educational package. Changes in vitamin intake were assessed using standard food frequency & 24-recall questionnaires. Results: Based on pre-test results, intake of vitamin B2, B6, B9, B12, and C were lower than Dietary Reference Intake (DRI) in both groups. Based on the post-test data, a significant increase occurred in the mean score of vitamin intake in the intervention group comparing with the control group; and also with the intervention group at pretest (P<0.05). Conclusion: TTM-based educational package could be effective in improving vitamin intake in urban female adolescents.